Reliability Evaluation of RV Reducers Based on Multi Degenerate Data - Li Jinfeng; Yang Yikun; Wang Xifeng; Yao Liangbo; Xiao Jianming (Jixie chuandong)
Aiming at the demand for reliability evaluation of RV reducers, the Gamma models, which can represent the performance degenerate process of reducers, are established respectively combining with transmission error data and backlash data of reducer performance degenerate test. A maximum likelihood estimation method is applied to estimate the parameters of degenerate models. Taking the models above as marginal distribution functions, a binary degenerate model of RV reducers is established through Copula function. The reliability and expected failure life of RV reducers are evaluated. The results show that the reliability evaluated by degenerate models based on transmission error and backlash is essentially in agree with the test results. The models can represent the degenerate process of RV reducers accurately. Gaussian Copula function is more suitable for representing the correlation between transmission error degenerate data and backlash degenerate data. Through the binary degenerate model, the expected failure life of RV reducers can be evaluated at different reliability under this working condition.